Auxin-cytokinin interaction and variations in their metabolic products in the regulation of organogenesis in two Eucomis species - Aremu, Adeyemi O; Plačková, Lenka; Pěnčík, Aleš; Novák, Ondřej; Doležal, Karel; Van Staden, Johannes (New biotechnology, 2016)
In the current study, we evaluated the effect of α-naphthaleneacetic acid (NAA) individually or in combination with different cytokinins (CKs) including benzyladenine (BA), meta-topolin (mT) and isopentenyladenine (iP) on organogenesis, auxin and CK content in Eucomis autumnalis subspecies autumnalis (EA) and Eucomis zambesiaca (EZ). These species were used as model plants due to their ornamental and medicinal properties. Three leaf explants were inoculated in screw-cap jars containing 30mL Murashige and Skoog (MS) media supplemented with 5μM NAA alone or in combination with 5μM CK (BA, mT or iP). After 10 weeks (EA) or 15 weeks (EZ), parameters including shoot and root growth as well as plant fresh weight were recorded. For analysis of auxin and CK content, whole plantlets were harvested, pooled and freeze-dried for the different treatments. In both species, shoot and root proliferation as well as plant biomass were generally higher when NAA was combined with the individual CK than in NAA or CK treatment. The highest concentration of indole-3-acetic acid (IAA, 619pmolg-1 DW) and 2-oxindole-3-acetic acid (OxIAA, 2381pmolg-1 DW) were observed in EA-treated with NAA alone while mT treatment (without NAA) had the most abundant indole-3-acetyl-l-aspartic acid (IAAsp, 904 and 582pmolg-1 DW for EA and EZ, respectively) in both species. A significant concentration of total endogenous CK accumulated in both Eucomis regenerants from mT and mT+NAA when compared to the other treatments. The majority of the detected CKs were of the aromatic CK-type, mainly free bases. The potential physiological roles of these quantified phytohormones in relation to the observed morphological responses are discussed.
Keywords: Asparagaceae; Phytohormones; meta-Topolin; kyseliny naftalenoctové; lékové interakce; Ornamentals; Drug Interactions; Biomass; výhonky rostlin; druhová specificita; Naphthaleneacetic Acids; Indoleacetic Acids; Species Specificity; cytokininy; Cytokinins; Indole-3-acetic acid; biotechnologie; Plant Roots; Rooting; kyseliny indoloctové; regulátory růstu rostlin; Plant Shoots; Biotechnology; biomasa; kořeny rostlin; Plant Growth Regulators